Swallowing of Casson fluid in oesophagus under the influence of peristaltic waves of varying amplitude - Pandey S.K.; Tiwari S.K. (My University, 2025)
The experimentally verified fact that there is a high pressure zone in the lower part of the oesophagus has established that the earlier models fall short of representing the realistic swallowing process in the oesophagus. Since the high pressure is created by gradually increasing amplitudes of peristaltic waves, swallowing of Casson fluid in oesophagus is mathematically remodeled. It is revealed that in the case of exponentially increasing amplitude, pressure is non-uniformly distributed for different cycles. Pressure increases along the entire length of the oesophagus; and finally toward the end of the oesophageal flow, it increases quite significantly, probably to ensure delivery into the stomach. This is a similar observation for Newtonian as well as non-Newtonian fluids but Casson fluids need more pressure; and hence more efforts are required by the oesophagus to transport the fluid forward. When wave amplitude is small, flow rates are small. In such a case, Casson fluid requires higher flow rates for reflux to occur in comparison to Newtonian fluid. This tendency gradually diminishes with increasing amplitude. For a particular value of amplitude, there is no difference; and beyond that the trends are quite opposite. Thus, Casson fluid is found to be less prone to reflux near the wall. It is also concluded that for the Newtonian fluid as well as for the non-Newtonian Casson fluid, reflux is more likely to occur with increasing amplitude and it is further augmented by the addition of amplifying parameter. © 2017 World Scientific Publishing Company.